2015
DOI: 10.2118/169104-pa
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Techniques for Foam Flow in Porous Media

Abstract: Foam, a dispersion of gas in liquid, has been investigated as a tool for gas-mobility and conformance control in porous media for a variety of applications since the late 1950s. These applications include enhanced oil recovery, matrix-acidization treatments, gasleakage prevention, as well as contaminated-aquifer remediation. To understand the complex physics of foam in porous media and to implement foam processes in a more-controllable way, various foam-modeling techniques were developed in the past 3 decades.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
93
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 114 publications
(241 reference statements)
0
93
0
1
Order By: Relevance
“…Local equilibrium models assume that foam lies in a local steady state. Ma et al (2015) concluded several local equilibrium models. Marfoe et al (1987) put forward a model which realized gas mobility reduction through gas viscosity alteration (Equation (2-13)).…”
Section: Local Equilibrium Modelmentioning
confidence: 99%
“…Local equilibrium models assume that foam lies in a local steady state. Ma et al (2015) concluded several local equilibrium models. Marfoe et al (1987) put forward a model which realized gas mobility reduction through gas viscosity alteration (Equation (2-13)).…”
Section: Local Equilibrium Modelmentioning
confidence: 99%
“…The reasons why foam is a good candidate driving fluid for improved oil recovery stem from a number of properties of foam, particularly the properties it exhibits when present within porous media such as oil reservoirs [4,5]. Using foam as a driving fluid, rather than using injected gas alone, tends to prevent gas (within the foam) from simply rising to the top of the reservoir and "overriding" the oil present [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A nonNewtonian uid model was used for the simulation of foam ow in oil pipes, and rheological parameters were obtained experimentally. 44 The simulation of foam ow in porous media can also be performed upon properly adapting the model to this system, but most methods for this task are based on a gasliquid two-phase ow model.…”
Section: Introductionmentioning
confidence: 99%